2022
DOI: 10.1002/jgc4.1637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic counselor disabilities on their professional experiences: A qualitative investigation of North American counselors' perceptions

Abstract: The National Society of Genetic Counselors' policies recognize the value of diversity in the profession. Yet North American genetic counselors are very homogeneous with respect to self-identified disabilities. One step towards diversifying the profession is understanding the experiences of genetic counselors who have disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Research is needed on experiences prior to graduate school (i.e., during the graduate school application and interview processes) as well as after graduate school (i.e., during the certification process and throughout the career), as participants suggested that there are also barriers to inclusion and opportunities for increased support at these stages. Darr et al's study provides some insight into the nature of these challenges, but additional research is needed to inform appropriate recommendations (Darr et al, 2023). Future research should also explore how intersectional identities may impact the experiences of genetic counseling students with disabilities and chronic illnesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research is needed on experiences prior to graduate school (i.e., during the graduate school application and interview processes) as well as after graduate school (i.e., during the certification process and throughout the career), as participants suggested that there are also barriers to inclusion and opportunities for increased support at these stages. Darr et al's study provides some insight into the nature of these challenges, but additional research is needed to inform appropriate recommendations (Darr et al, 2023). Future research should also explore how intersectional identities may impact the experiences of genetic counseling students with disabilities and chronic illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is only one published study on the experiences of genetic counselors with disabilities as they navigate their careers (Darr et al, 2023). The findings of this study suggest that genetic counselors with disabilities are faced with many of the same academic and professional challenges that have been reported by other medical providers with disabilities, including stigma, lack of accessibility, and the burden of self‐advocacy.…”
Section: Introductionmentioning
confidence: 99%